Sources and manifestations of childhood stress - Jurin, Tanja; Staničić, Ana (2010)
Objective: To determine the sources of stress, in particularly the content of fear and its psychological and physical manifestations in school children. Methods: The study was conducted on a sample of 130 male and 139 female pupils, aged between 10 and 14, from a single elementary school in Zagreb. Sources of stress (estimated levels of stress in specific areas of pupils’ life), physical manifestations of stress (a silhouette on which they indicated on which parts of the body they felt stress), content of fears which pupil’s would like the most to disappear and psychological manifestations of stress (depression, anxiety, anxiety sensitivity and self-respect) were examined. Results: The strongest source of stress for children of both genders is school. School and parents present higher sources of stress in children of 13 and 14 years of age in regard to younger children (10-12 year olds). Physical manifestations of stress are different in girls and boys. The overall intensity of a child’s experienced stress was found to be associated with lower self-esteem higher anxiety and depression. Children report a vast array of fears, but the most frequent one among our sample is school. Although dominant amongst pupils of both genders, girls more frequently reported a fear of school. Some specific fears correlate with measures of depression, trait anxiety, anxiety sensitivity and self-esteem. Conclusion: The results of this study indicate gender and age differences in the sources and manifestations of stress throughout childhood.
Projekt MZOS
ENG